Pengaruh Strategi Pembelajaran PQ4R ( Preview, Question, Read, Reflect, Recite, Review) Terhadap Hasil Belajar Ilmu Pengrtahuan Alam terpadu Siswa madrasah Tsanawiyah Negeri 01 Kepahiang. - Fetri Yenti (Jurnal Pendidikan Guru, 2020)
The purpase ofthis studybwas to determine the effect of the PQ4R Learning strategy (preview, Questin, Read, Reflelect, recite, Review ) on the learning outcomes of inttegrated Science in islamic education in Biology learning. This resarch is a quasi-exsperimental study using the posttest-Only Control desingn while data colelection is done using a test instrument.The sample of the study was class IXB (experimental class) totaling 26 students and class IXA (control Class) totaling 26 Students. The research data obtained the highest score in the exsperimental class was 95 and the lowest score was 45 wint an average of 72,3, while in the control class the highest score was 80 and the lowest score was 40 with an average 64,03. Based on the calculation using the test obtained thitung = 2,28 and at a significant level of 5% obtained table = 2,28 and significance lovel of 1% Table =2,28 thus So that Ha is accapted meaning that there is a significant influence on the results of integrated Science Learning of students who use the PQ4R learning strategi ( preview, question, read, Reflect, Recile, Review) in the Madrasah Tsanawiyah Negeri 01 Kepahiang.